Evaluating The Effectiveness Of Tobacco Prevention Programs: A survey Of Arab Secondary Schools In Kuala Lumpur - Elrasheed, . Mutasim (Gezira Journal of Educational Sciences and Humanities, 2018)
This study aims at evaluating the effectiveness of tobacco prevention programs. The descriptive method was adopted and a questionnaire was applied. The data was analyzed by using (SPSS) program. The sample consisted of 63 teachers (30) males – 33 females), selected from three of Arab secondary schools in Kuala Lumpur. Study results showed that there were no differences of statistical significance in the implementation of policies between teachers and no differences in the training and skills. Results also showed that there were no differences in providing knowledge of programs and support sessions between teachers. There were no differences in policies, training and providing knowledge between males and females. The significance of this result is that tobacco prevention programs were not effective in all the surveyed schools in all parts of programs, policies, training, skills implementation and providing knowledge to students and staff.